Validitas Model Pembelajaran DOTISC (Direction, Organization, Tutoring, Implementation, Solution, and Confirmation) untuk Pembelajaran IPA di SMP - Aulya Nanda Prafitasari; Sudarti Sudarti; I Ketut Mahardika (Program Studi Magister Pendidikan IPA FKIP Universitas Jember Bekerjasama dengan Perkumpulan Pendidik IPA Indonesia (PPII), 2016)
Science education learning isn’t passive only from teachers, but also students are required to be active with direct experience to develop their potential to gain a deep and long-term understanding. But the differences of student’s ability is one of problems in science learning. Teacher needs innovative learning model that can optimize the capabilities of each student and work together in achieving the learning objectives. Therefore, DOTISC (Direction, Organization, Tutoring, Implementation, Solution, and Confirmation) learning model needs to be develop. The purpose of this study to describe the validity of DOTISC learning model for learning science in junior high school. Data were analyzed descriptively based on the score sheet of expert validation, user validation, and audience validation. In addition to manually, audience validation using SPSS for Windows. The learning model DOTISC declared valid based on a percentage of expert validation is 79.17%, 80.36% from user validation, and audience validation is 80.40%.